Song of the mango and other new myths - Borja, Vida Cruz- (Bughaw, 2022)
A diwata brings a grieving slave’s brother back to life as a mango tree. Two writers write their ideal lovers into existence with ink from a mangkukulam. A kapre and a farmgirl play out a tale as old as time in Spanish colonial Philippines. A girl with a magical heritage must rescue a bumbling cartographer from the hidden city of Biringan. Maria Makiling opens a pop-up café with human heartbreak on the menu.